Dynamics of triadin, a muscle-specific triad protein, within sarcoplasmic reticulum subdomains - Sébastien, Muriel (Mol Biol Cell, 2020)
In skeletal muscle, proteins of the calcium release complex responsible for the excitation-contraction (EC) coupling are exclusively localized in specific reticulum–plasma membrane (ER-PM) contact points named triads. The CRC protein triadin (T95) is localized in the sarcoplasmic reticulum (SR) subdomain of triads where it forms large multimers. However, the mechanisms leading to the steady-state accumulation of T95 in these specific areas of SR are largely unknown. To visualize T95 dynamics, fluorescent chimeras were expressed in triadin knockout myotubes, and their mobility was compared with the mobility of Sec61β, a membrane protein of the SR unrelated to the EC coupling process. At all stages of skeletal muscle cells differentiation, we show a permanent flux of T95 diffusing in the SR membrane. Moreover, we find evidence that a longer residence time in the ER-PM contact point is due to the transmembrane domain of T95 resulting in an overall triad localization.